A cross-exchange comparison of execution costs and information flow for NYSE-listed stocks - BESSEMBINDER, H; KAUFMAN, H (Journal of Financial Economics, 1997)
We examine execution costs for trades in NYSE issues completed on the NYSE, the NASD dealer market, and the regional stock exchanges during 1994. We find that effective bid-ask spreads are only slightly smaller at the NYSE. However, realized bid-ask spreads, which measure market-making revenue net of losses to betterinformed traders but gross of inventory or order-processing costs, are lower on the NYSE by a factor of two to three. This differential is attributable to the successful ‘cream skimming’ of uninformed trades by off-NYSE market makers. These findings reinforce existing concerns about whether orders are routed so as to receive the best possible execution.